Heterologous immunization with adenovirus vectored and inactivated vaccines effectively protects against SARS-CoV-2 variants in mice and macaques - He, Qian; Mao, Qunying; Zhang, Jialu; Gao, Fan; Bai, Yu; Cui, Bopei; Liu, Jianyang; An, Chaoqiang; Wang, Qian; Yan, Xujia; Yang, Jinghuan; Song, Lifang; et al. (Frontiers in Immunology, 2022)
To cope with the decline in COVID-19 vaccine-induced immunity caused by emerging SARS-CoV-2 variants, a heterologous immunization regimen using chimpanzee adenovirus vectored vaccine expressing SARS-CoV-2 spike (ChAd-S) and an inactivated vaccine (IV) was tested in mice and non-human primates (NHPs). Heterologous regimen successfully enhanced or at least maintained antibody and T cell responses and effectively protected against SARS-CoV-2 variants in mice and NHPs. An additional heterologous booster in mice further improved and prolonged the spike-specific antibody response and conferred effective neutralizing activity against the Omicron variant. Interestingly, priming with ChAd-S and boosting with IV reduced the lung injury risk caused by T cell over activation in NHPs compared to homologous ChAd-S regimen, meanwhile maintained the flexibility of antibody regulation system to react to virus invasion by upregulating or preserving antibody levels. This study demonstrated the satisfactory compatibility of ChAd-S and IV in prime-boost vaccination in animal models.